Governmental Accounting: Procedures and Practices, 1985 (Book). - Freeman, Robert J.; Hendrickson, Harvey S. (The Accounting Review, 1986)
Reviews the book "Governmental Accounting: Procedures and Practices, 1985," 2nd ed., by Cornelius E. Tierney and Philip T. Calder.